Rapid-SF: A Rapid Whole-Blood Screen for Soluble Fibrin Monomer - Hay, Karen L.; Bull, Brian S. (Thrombosis and Haemostasis, 2002)
Thrombosis accounts for a high proportion of disability and death in the West. Although soluble fibrin (SF) assays have been shown to be good predictors of thrombosis, current quantitative assays are too complex or lengthy to provide timely results, while simpler methods are qualitative and lack sensitivity. We here describe a rapid, new, protamine-based whole-blood screening method for SF which is quantitative and suitable for point-of-care use. Citrated whole blood is mixed with reagent under controlled conditions and the time until development of an SF precipitate is measured. Negative samples remain precipitate-free for 300 seconds. Strongly positive samples develop precipitate in as little as 10 seconds. SF times are mathematically converted to arbitrary SF units (SFU). This Rapid-SF test provides a simple and reliable means of detecting the presence of SF, and is well-suited for whole-blood rapid screening in the emergency department, operating room or clinic.
Keywords: Disseminated intravascular coagulation; fibrin-analysis; thrombosis diagnosis; soluble fibrin; paracoagulation